Modeling and Control of Instabilities in Combustion Processes - Pušenjak, Rudolf; Oblak, Maks (Anali PAZU, 2022)
This paper treats the control of nonstationary oscillations of acoustic pressure in the combustion instability process, which appears in the combustion chamber. Two models of nonstationary combustion process control are presented, where first of them is a classic model, which applies the Rayleigh criterium of phase matching between heat-release rate and acoustic pressure. The second model is an alternative van der Pol model exhibiting selfexciting oscillations due to the feedback with a negative damping. The paper outlines the model of fuel control, which is successfully applied for quenching of selfexcited oscillations. Efficiency of fuel control to quench selfexcited oscillations is shown in the phenomenon of competitive quenching, where the influence of various control parameters is explained.
Keywords: instability of combustion process; selfexcited pressure oscillations; multiplicative feedback control function; EL-P method